2022
DOI: 10.3390/mi13122102
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Event-Hardened Scheme of Phase-Locked Loop Microsystems for Aerospace Applications

Abstract: In order to improve the ability of the phase-locked loop (PLL) microsystem applied in the aerospace environment to suppress the irradiation effect, this study presents an efficient charge pump hardened scheme by using the radiation-hardened-by-design (RHBD) technology. In this study, the sensitivity analysis of the single-event transient (SET) at different nodes of charge pump and different bombardment energies is carried out. Without changing the original structure and loop parameters, a hardened scheme of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Therefore, using the radiation-hardened-by-design (RHBD) technology to reinforce the CP and voltage-controlled oscillator (VCO) can reduce the sensitivity of the PLL to the singleevent effect [9,10]. The author has put forward an effective radiation hardening scheme for the CP in the previous work [11], and this work focuses on the radiation hardening design of the VCO module.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, using the radiation-hardened-by-design (RHBD) technology to reinforce the CP and voltage-controlled oscillator (VCO) can reduce the sensitivity of the PLL to the singleevent effect [9,10]. The author has put forward an effective radiation hardening scheme for the CP in the previous work [11], and this work focuses on the radiation hardening design of the VCO module.…”
Section: Introductionmentioning
confidence: 99%
“…The soft error performance before and after radiation in DG TFETs 6T SRAM cells have also been studied. Xiang et al showed the effect of single-event transient (SET) in a phase-locked loop and proposed an SET-hardened structure to improve the irradiation resistance of PLL [ 4 , 5 ]. Since the transistor device in this work is graphene-based, it is important to highlight the effects of radiation on graphene and graphene-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…performance before and after radiation in DG TFETs 6T SRAM cell are also studied. Xiang et al showed the effect of single event transient (SET) in a phase locked loop and proposed SET-hardened structure to improve the irradiation resistance of PLL [4,5]. Note that it has been shown theoretically and experimentally that graphene nano-ribbon FET (GNRFET) can potentially replace planar CMOS and FinFET [6].…”
Section: Introductionmentioning
confidence: 99%